Peripherally Inserted Central Catheters in Pediatric Oncology Patients: A 15-Year Population-based Review From Maritimes, Canada. Issue 1 (January 2018) - Borretta, Lisa; MacDonald, Tamara; Digout, Carol; Smith, Nadine; Fernandez, Conrad V.; Kulkarni, Ketan
Abstract : The present population-based study evaluates the management and complications of peripherally inserted central catheters (PICC) in all pediatric oncology patients diagnosed in Maritimes, Canada from 2000 to 2014. A total of 107 PICCs were placed in 87 (10.1%) pediatric oncology patients. A high percentage (33% and 44%, respectively) of the first and second PICC lines was associated with complications. Thrombosis, occlusion, and infection were the most frequent complications. Age above 10 years and left body side of insertion were significantly associated with PICC complications. Given the frequent use of PICCs and the high incidence (>33%) of complications, there is a need to mitigate PICC line complications.